A Novel, Highly Related Jumbo Family of Bacteriophages That Were Isolated Against Erwinia - Sharma, Ruchira; Pielstick, Brittany A.; Bell, Kimberly A.; Nieman, Tanner B.; Stubbs, Olivia A.; Yeates, Edward L.; Baltrus, David A.; Grose, Julianne H. (Frontiers in Microbiology, 2019)
Erwinia amylovora is a plant pathogen from the Erwiniaceae family and a causative agent of the devastating agricultural disease fire blight. Here we characterize eight lytic bacteriophages of E. amylovora that we isolated from the Wasatch front (Utah, USA) that are highly similar to vB_EamM_Ea35-70 which was isolated in Ontario, Canada. With the genome size ranging from 271-275 kb, this is a novel jumbo family of bacteriophages. These jumbo bacteriophages were further characterized through genomic and proteomic comparison, mass spectrometry, host range and burst size. Their proteomes are highly unstudied, with over 200 putative proteins with no known homologs. The production of 27 of these putative proteins was confirmed by mass spectrometry analysis. These bacteriophages appear to be most similar to bacteriophages that infect Pseudomonas and Ralstonia rather than Enterobacteriales bacteria by protein similarity, however we were only able to detect infection of Erwinia and the closely related strains of Pantoea.